(untitled) - Yewdall, David Lewis (Burlington, MA, 2007)
Focusing on the subject of sound for films, this title provides real-life examples and relevant technical data. It covers popular sound editing systems such as Pro Tools and Final Cut Pro
Keywords: Television broadcasting,Sound motion pictures,Television,Hình ảnh chuyển động âm thanh; Sound effects